Strategy for developing discipline character through rewards and punishments in vocational high school: - Triyono Triyono; Tri Kuat; Mohammad Omar AL-Momani (Jurnal Taman Vokasi, 2025)
This research aims to: (1) Analyze strategies growth character Teacher attendance discipline at Muhammadiyah 1 Playen Vocational School, (2) Analyzing strategies growth character Teacher attendance discipline at Muhammadiyah 1 Playen Vocational School, (3) Analyzing implications growth The character of teacher attendance discipline at SMK Muhammadiyah 1 Playen This strategy is expected to be able to create a more conducive work environment and improve the quality of education at SMK Muhammadiyah 1 Playen. This study uses a qualitative research method with a research location at SMK Muhammadiyah 1 Playen. The research subjects include teachers, principals, vice principals, and students. Data collection techniques are carried out through in-depth interviews, while data analysis is carried out using Atlas.ti 8 software to group and interpret data systematically. The results of the research carried out were (1) strategies for developing teacher discipline character through rewards and punishments. includes (a) measuring instruments (b) warnings . (2) the form of implementing the development of teacher discipline character through rewards and punishments includes (a) the form of rewards and punishments (b) method,(3) The implications of developing the character of teacher discipline through rewards and punishments are that (a) the disposition is right on target (b) human resources are more disciplined (c) communication between superiors and subordinates becomes more focused.